Low levels of genetic structuring in King George whiting Sillaginodes punctatus across two geographic regions. Issue 2 (7th December 2017) - Kent, J.; Jenkins, G.; Sherman, C. D. H.
Abstract : Postlarvae of King George whiting Sillaginodes punctatus, a commercially important fish species in southern Australia, were collected from multiple locations across south and south‐eastern Australia. Genetic analyses using seven microsatellite markers found little evidence of genetic structure suggesting high levels of connectivity between the regions. The results found no evidence of a distinct source spawning population within the south‐eastern range sampled in this study.